Behavior of Self Compacting Reinforced Concrete One Way Bubble Deck Slab - Yaagoob, Ali H.; Harba, Ibrahem S. (Al-Nahrain Journal for Engineering Sciences, 2020)
Reinforced concrete slab with plastic voids (Bubbled Deck system) is a new type of slabs which has two-dimensional arrangement of voids within the slab that is developed to decrease the slab self-weight while maintaining approximately the same load carrying capacity as compared with the solid slabs. Plastic voided slabs have the ability to reduce concrete amount by about 30 percent and this reduction is so important in terms of cost saving and enhancement the structural performance. In this research paper investigation is carried out to study the shear strength behavior of one-way bubble deck slab using self-compacting reinforced concrete. The experimental program consists of testing thirteen one-way slabs with dimensions of (1700 length, 700 width and 150 thick) mm. One of the tested slabs is a solid slab (without balls) is used as a reference, the remaining twelve bubbled slabs with ball diameter (73, 60) mm are divided into five groups according to the parameters of the experimental work, the parameters of the experimental work include: type of slab (bubble and solid slabs), ball diameter (73, 60) mm, shear reinforcement and spacing between balls. The experimental results showed that the bubbled slabs without shear reinforcement have a decrease in the ultimate load as compared to solid slab by about 3.7% to 14.3% and an increase in the deflection at ultimate load by about 10% to 22%, at the same time the first crack load decreases by about 15.3% to 42.4% as compared to solid slab due to decreases of moment of inertia of bubble slab compared to solid slab. Also, the results showed that the bubbled slabs withe shear reinforcement (multi-leg) have an increase in the ultimate load as compared to solid slab by about 35.4% to 57.3% and an increase in the deflection at ultimate load by about 1% to 15%, at the same time the first crack load decreases by about 2.8% to 27.4% as compared to solid slab.